An Analysis of Equity and Accountability in MGNREGS : A Study of Haryana in India - Verma, Neera; Saharan, Sarina (Arthshastra Indian Journal of Economics & Research, 2019)
Launched in 2006, the Mahatma Gandhi National Rural Employment Guarantee Scheme (hereafter referred to as MGNREGS) is the largest and most ambitious employment generation program to ensure livelihood security in rural India. This paper examined how far MGNREGS supported equity and accountability of the state in the economic sphere. The equity aspect was examined through the inclusion of the weaker sections (Scheduled Castes) and women workers in the scheme. The equity aspect of MGNREGS was examined in terms of both the issuance of job cards to Scheduled Castes and the total number of person - days generated for Scheduled Castes and the participation of women over the years. Further, accountability under the scheme was analyzed by using parameters such as release and utilization of funds under the scheme, work provided within 15 days of demand for work, officers’ visit at worksites, unemployment allowance, participation in social audit, and role of Gram Sabha. The study found that MGNREGS had, by and large, promoted equity through inclusion of Scheduled Caste households in proportion to the job cards issued to the marginalized section. The share of Scheduled Caste households was close to 50% on an average for the period from 2005-06 to 2015-16. One of the most important findings of the study was that adequate funds were not being released under the scheme, and the actual allocated funds had dwindled to 7% of the required funds to provide 100 days employment to all job card holders in a year. This questioned the very claim of MGNREGS as a demand-driven scheme.